145k views
3 votes
Rewrite the equation x + y + 3 = –2x + 4y + 18 into standard form (ax + by = c)

A. x – y = 5
B. x – y = 15
C. 3x –3y = 5
D. x + y = 5

User YON
by
5.5k points

1 Answer

7 votes

Answer:

Choice A is correct answer.

Explanation:

Given equation is:

x+y+3 = -2x+4y+18

Adding 2x to both sides of above equation, we get

2x+x+y+3 = 2x-2x+4y+18

3x+y+3 = 0+4y + 18

Adding -4y to both sides of above equation,we get

3x+y+3 -4y = 4y+18-4y

3x-3y+3 = 18

Adding -3 to both sides of above equation, we get

3x-3y+3-3 = 18-3

3x-3y = 15

Taking 3 common to both sides of above equation, we get

3(x-y) = 3(5)

Hence, x-y = 5 where a = 1 , b = -1 and c = 5

User Michele Carino
by
5.8k points